2021
DOI: 10.1098/rsif.2021.0518
|View full text |Cite
|
Sign up to set email alerts
|

Flight efficiency is a key to diverse wing morphologies in small insects

Abstract: Insect wings are hybrid structures that are typically composed of veins and solid membranes. In some of the smallest flying insects, however, the wing membrane is replaced by hair-like bristles attached to a solid root. Bristles and membranous wing surfaces coexist in small but not in large insect species. There is no satisfying explanation for this finding as aerodynamic force production is always smaller in bristled than solid wings. This computational study suggests that the diversity of wing structure in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…Bristle diameter was ~1.1 mm or ~8.8 × 10 −3 wing length and the bristle angle α b relative to the wing's longitudinal axis was ~29 • (Figures 1h and 2e). The model wing was comparatively rigid as direct measurements have recently shown that real wing bristles are remarkably stiff [30] and we also numerically showed that bristle bending is likely to be negligible during wing flapping in tiny insects [29]. The wings had little weight under the tested conditions because of neutral buoyancy resulting from the similar densities of the PVA (~1190-1310 Kg m −3 ) and the fluid used (glycerin, ~1260 Kg m −3 ).…”
Section: Wing Design and Kinematicsmentioning
confidence: 68%
See 4 more Smart Citations
“…Bristle diameter was ~1.1 mm or ~8.8 × 10 −3 wing length and the bristle angle α b relative to the wing's longitudinal axis was ~29 • (Figures 1h and 2e). The model wing was comparatively rigid as direct measurements have recently shown that real wing bristles are remarkably stiff [30] and we also numerically showed that bristle bending is likely to be negligible during wing flapping in tiny insects [29]. The wings had little weight under the tested conditions because of neutral buoyancy resulting from the similar densities of the PVA (~1190-1310 Kg m −3 ) and the fluid used (glycerin, ~1260 Kg m −3 ).…”
Section: Wing Design and Kinematicsmentioning
confidence: 68%
“…This study used generic wings with bristle spacing similar to that of small insects (Figure 1a-g, Table 1) [29] instead of testing the bristled wings of any single specific species. Our synthetic wing shapes were constructed to consider three aspects: a resemblance to natural flapping bristled wings; a one-parameter family that determined wing permeability (bristle spacing); and an emphasis on aerodynamics and power.…”
Section: Wing Design and Kinematicsmentioning
confidence: 99%
See 3 more Smart Citations